Pendampingan Baca Tulis Al-Qur’an Bagi Anak Usia Dini Di TPQ Darussalam Sumbersari Kediri - Misbahul Huda (LP3M IAIFA Kediri, 2023)
This community service activity is through attracting community participation to allow their children to learn the Koran. The objectives of the activity are; To recognize hijaiyah letters. The coaching program is carried out through assistance in eradicating illiteracy in the Koran through the Iqra method. Initial observations through interviews with religious leaders and several communities stated that children were less interested in the Koran at TPQ because they had to queue for a long time at one Koran teacher so that they felt bored and ended up decreasing their concentration and enthusiasm for learning the Koran. This activity is divided into three classics, namely; Opening activities (early classics), core activities and closing activities (late classics). The existence of a place to study the Koran at the DARUSSALAM Mosque every night, becomes a means to gather and interact with each other, in addition to being a means to meet other children with one another, is also very important for the children of Panggungsari Hamlet. because with this learning facility it can increase knowledge to children, especially in terms of correct and precise reading of the Qur'an through learning Iqra. With this activity as an alternative to learning the Koran, it is very beneficial for children who previously only spent their days playing and with busy parents who sometimes make children less attention from their parents.